2003
DOI: 10.1111/j.1523-1747.2003.12605.x
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylfumarate Is a Potent Inducer of Apoptosis in Human T Cells

Abstract: Fumaric acid esters (FAE) have been used for the systemic treatment of psoriasis in Germany for almost 50 years. Recently, it has been shown that dimethylfumarate (DMF) as the main ingredient of the marketed FAE mixture is a potent inhibitor of the nuclear transcription factor NF-kappaB. DMF was also shown to induce apoptosis in various cells. Because T cells play a crucial role in psoriasis pathogenesis, we asked whether DMF and its main metabolite methylhydrogenfumarate (MHF) were able to induce apoptosis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
165
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(177 citation statements)
references
References 29 publications
10
165
1
1
Order By: Relevance
“…The observed reductions in cytokine secretion were dose dependent and restricted to DMF; pretreatment with MMF did not significantly reduce cytokine/chemokine production. As fumarates have been previously shown to alter viability and proliferation of peripheral and CNS‐resident cells,8, 28 we assessed whether the changes in cytokine and chemokine levels were due to changes in viability or proliferation. Following pretreatment with DMF, MMF, or vehicle no reductions in viability or proliferation were observed (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed reductions in cytokine secretion were dose dependent and restricted to DMF; pretreatment with MMF did not significantly reduce cytokine/chemokine production. As fumarates have been previously shown to alter viability and proliferation of peripheral and CNS‐resident cells,8, 28 we assessed whether the changes in cytokine and chemokine levels were due to changes in viability or proliferation. Following pretreatment with DMF, MMF, or vehicle no reductions in viability or proliferation were observed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…DMF can induce apoptosis in circulating immune cells, including lymphocytes and monocytes,8, 9 and exerts anti‐inflammatory effects on both peripheral and CNS‐resident immune cells 3, 10, 11. Recent reports have demonstrated that the Nrf2‐dependent induction of AREs by DMF may be dispensable for neuroprotection, and the influence of DMF on both the innate and adaptive immune response may be the principle mechanism of action 12.…”
Section: Introductionmentioning
confidence: 99%
“…DMF interferes with the glutathione system, heme oxygenase 1, and the Nrf2 pathway. 46,[55][56][57][58] Yet, the most prominent interaction in the induction of cell death by DMF is inhibition of NF-kB signaling 18,21,51 ; however, the exact mechanism of DMF-induced NF-kB inhibition has not yet been completely elucidated. We showed that DMF treatment decreases DNA binding of the NF-kB subunit p65 and to a smaller extent p50 and RelB and thus impairs transcriptional activity of NF-kB.…”
Section: Discussionmentioning
confidence: 99%
“…As opposed to resting T cells (D0), activated T cells (D6) depend on NF-kB. 37 Upon DMF treatment, activated, but not resting, healthy T cells were shown to undergo cell death, reflecting selective cell death induction by DMF in cells with high NF-kB activity 18,21,37 (supplemental Figure 1C). Experiments with CTCL cell lines corroborated these results.…”
Section: Dmf Induces Cell Death In Patient-derived Ctcl and Ctcl Cellmentioning
confidence: 99%
“…The first in vitro studies with nonphysiological, high concentrations of fumaric acid esters pointed at proapoptotic effects on T-cells [Treumer et al 2003]; a mechanism which is unlikely to be the main mechanism operative in vivo. Further experiments with cultured peripheral mononuclear blood cells disclosed anti-inflammatory properties of DMF with a dose-dependent ability to promote so called T-helper cell type 2 (Th2) immune responses characterized by the production of interleukin-(IL)4, or IL-5 [de Jong et al 1996].…”
Section: Dimethyl Fumarate: Pharmacokinetic Datamentioning
confidence: 99%